2020
DOI: 10.1007/s00216-020-02749-8
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous analysis of multiple oligonucleotides by temperature-responsive chromatography using a poly(N-isopropylacrylamide)-based stationary phase

Abstract: Oligonucleotide therapeutics have contributed remarkably to healthcare, being well suited for the treatment of intractable diseases that are difficult to approach using conventional drug modalities. However, as common techniques of oligonucleotide analysis rely on reversed-phase or ion-exchange liquid chromatography and thus employ toxic organic solvents and/or ion-pairing reagents, better alternatives are highly sought after. Poly(N-isopropylacrylamide) (PNIPAAm) is widely used in temperatureresponsive chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 40 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…The chromatography system uses all-aqueous mobile phases, although the addition of a small amount of methanol is required to improve detection with mass spectroscopy 28 . To improve the performance of chromatography systems, various types of PNIPAAm copolymer have been investigated such as the copolymerization of hydrophobic monomers to enhance hydrophobic interaction 29 32 and the copolymerization of ionic monomers to utilize electrostatic interaction besides hydrophobic interaction 33 37 . Moreover, several types of PNIPAAm configuration on silica bead surfaces have been investigated using various polymerization methods 4 , 38 40 .…”
Section: Introductionmentioning
confidence: 99%
“…The chromatography system uses all-aqueous mobile phases, although the addition of a small amount of methanol is required to improve detection with mass spectroscopy 28 . To improve the performance of chromatography systems, various types of PNIPAAm copolymer have been investigated such as the copolymerization of hydrophobic monomers to enhance hydrophobic interaction 29 32 and the copolymerization of ionic monomers to utilize electrostatic interaction besides hydrophobic interaction 33 37 . Moreover, several types of PNIPAAm configuration on silica bead surfaces have been investigated using various polymerization methods 4 , 38 40 .…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated the separation of eight steroid compounds having different chemical structures and different numbers of hydroxyl groups. Isolation and purification of biological molecules such as peptides, proteins, saccharides and nucleosides are indispensable technology in the fields of proteomics, genomics, and glycomics [40][41][42]. Further study for the separation of bio-related molecules using Sil−VPG 15 is currently underway and will be reported in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In conventional RPLC, the separation of S-oligos require an organic solvent with an ion-pairing reagent, such as tetraethylamine-acetic acid, as the mobile phase and gradient elution. In contrast, Maekawa et al reported recently that good separation of multiple phosphorothioated oligonucleotides was obtained by TR-HPLC using a P(NIPAAm-co-BMA-co-DMAPAAm) hydrogel-modified column with an aqueous solvent and an isocratic elution without ion-pairing reagents 62 .…”
Section: Oligonucleotide Separation Using a P(nipaam-co-bma-co-dmapaam) Hydrogel-modified Columnmentioning
confidence: 92%
“…The retention of oligonucleotides was increased by increasing the temperature, opposite to the behavior exhibited by conventional RPLCs. The separation of single nucleobases in oligonucleotides, such as guanine (G), cytosine (C), thymine (T), or adenine (A), was also achieved using the P(NIPAAm-co-BMA-co-DMAPAAm) hydrogel-modified column 62 .…”
Section: Oligonucleotide Separation Using a P(nipaam-co-bma-co-dmapaam) Hydrogel-modified Columnmentioning
confidence: 99%